Analisis Perbandingan Abnormal Return dan Trading Volume Activity Sebelum dan Sesudah Diumumkan Kasus Pertama Covid-19 di Indonesia - Novianti Wulandari; Nana Adriana (JEM Jurnal Ekonomi dan Manajemen, 2022)
This study aims to analyze the comparison of abnormal returns and trading volume activity before and after the announcement of the first case of Covid-19 in Indonesia on Monday 2 March 2020 (a case study on gold, oil, and gas mining companies listed on the Indonesia Stock Exchange). used are 21 days 10 days before the incident, 10 days after the incident, and the day the Covid-19 incident occurred. This type of research is an event study. The population in this study are all gold, oil and gas mining companies listed on the Indonesia Stock Exchange. The sample selection technique was purposive sampling and obtained 7 companies that met the testing criteria in the researcher's research. The parametric analysis test tool used to test the hypothesis in this study is the paired sample t-test. The results of this study indicate that: (1) The incidence of Covid-19 has no effect on abnormal returns, meaning that there is no significant difference in the average abnormal return between before and after the announcement of the first case of Covid-19 in Indonesia on Monday, March 2, 2020. (2) The COVID-19 event also has no effect on trading volume activity, meaning that there is no significant difference in average trading volume activity between before and after the announcement of the first Covid-19 case in Indonesia, Monday, March 2, 2020.